Predictive Value Of Left Atrial Volume Index And Right Ventricular Dilatation In Mitral Stenosis For Atrial Fibrillation. - Abdulmelik Yildiz (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Purpose: To examine the predictive value of left atrial volume index (LAVI) and right ventricular dilatation in mitral stenosis (MS) for atrial fibrillation (AF) and to determine the cut-off value. Materials and Methods: 14 men, 92 women, a total of 106 cases between the ages of 23-86 (mean: 50.7 +/- 12.7) with mitral stenosis were included in the study. All echocardiographic assessments were performed according to the criteria of American Society of Echocardiography (ASE). Patients were divided into two groups as AF and normal sinus rhythm (NSR). 39 patients with AF were classified as AF group and 67 patients with normal sinus rhythm were classified as NSR group. The demographic, clinical, echocardiographic characteristics of these two groups were compared. For the statistical analysis of datas, Kolmogorov-Smirnov, T-test, Mann-Whitney-U test and ROC analysis were used. Results: In mitral valve stenosis, left atrial volume index and right ventricular diastolic diameter increase. LAVI cut-off value for atrial fibrillation is 40,74 ml/m2, the sensitivity and specificity of it was found to be as 80% and 80.6%, respectively (PPV = 69.0%, NPV = 88.5%). Cut-off value of right ventricular diastolic diameter (RVDD) for atrial fibrillation is 36.7 mm, the sensitivity and specificity of it was found to be as 62.9% and 59.7%, respectively (PPV = 46.0%, NPV = 75.5%). Conclusion: It has been concluded that, there are cut-off values of LAVI and RVDD for the development of atrial fibrillation in mitral stenosis and to know those values that were important in determining treatment strategies. [Cukurova Med J 2014; 39(4.000): 772-778]